2019
DOI: 10.1016/j.psyneuen.2018.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Associations among maternal socioeconomic status in childhood and pregnancy and hair cortisol in pregnancy

Abstract: Dysregulation of the maternal-fetal hypothalamic-pituitary-adrenal axis (HPAA) has been hypothesized to negatively influence various offspring physical and mental health outcomes. Limited data suggest that low maternal socioeconomic status (SES) in pregnancy may disrupt maternal HPAA functioning. Research is needed that examines how maternal SES in childhood may influence maternal HPAA functioning in pregnancy, given evidence that early life adversity can have persistent effects on physiological stress reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 50 publications
5
26
0
Order By: Relevance
“…Generally, cortisol levels increase during pregnancy (physiological mechanisms reviewed by de Weerth & Buitelaar, ). Several researchers have shown that hair cortisol levels reliably increase throughout pregnancy (Bosquet Enlow et al, ; Bowers et al, ; Braig et al, ; D'Anna‐Hernandez, Ross, Natvig, & Laudenslager, ; Scharlau et al, ). Taking into account these normative physiological changes, researchers have assessed the effects of pregnancy cortisol on various outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, cortisol levels increase during pregnancy (physiological mechanisms reviewed by de Weerth & Buitelaar, ). Several researchers have shown that hair cortisol levels reliably increase throughout pregnancy (Bosquet Enlow et al, ; Bowers et al, ; Braig et al, ; D'Anna‐Hernandez, Ross, Natvig, & Laudenslager, ; Scharlau et al, ). Taking into account these normative physiological changes, researchers have assessed the effects of pregnancy cortisol on various outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty in trying to understand the socioeconomic impact on outcomes such as neonatal anthropometric measurements across race is in discerning the contextual framework of one’s socioeconomic status. Specifically, life course theories describe how experience across a woman’s lifetime may have a greater influence on birth outcomes compared with those around the time of childbirth [ 33 , 38 , 39 ]. One longitudinal study described differences in health outcomes among poor black, Puerto Ricans and whites of the same income, and found that disparities in health outcomes of blacks and Puerto Ricans relative to their white counterparts could be explained by the concentration of high poverty in the neighborhoods in which blacks and Puerto Ricans reside [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, we have accounted for variables from the postnatal period (the infant's first year of life) that may create a stressful environment for the infant. These factors include the family's SES, maternal psychopathology symptoms, maternal feelings about the relationship with their infant, infant exposure to tobacco smoke, and breastfeeding status (Ahnert et al, 2004;Bosquet Enlow et al, 2019;Brennan et al, 2002;Gunnar & Donzella, 2002;J. A. Ludmer et al, 2015;Martinez-Torteya et al, 2015;Tarullo & Gunnar, 2006).…”
Section: Discussionmentioning
confidence: 99%